APLIKASI SENYAWA AMIDA HUMAT SEBAGAI IONOFOR DALAM MEMBRAN ELEKTRODA SELEKTIF ION Ni (II) - Muhali Muhali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
The amide compound derived from humic acid has been applied as ionophore in ion selective electrode (ISE) measurement based on poly vinyl chloride (PVC) membrane.  The carboxylic acid group of the humic acid was first modified to the corresponding amide and is expected to form complex with the target cation. This work aims at obtaining selectivity coefficient towards Ni2+ ion.  The products of the reactions were observed using infra red (IR) spectrometer.  The amide compound derived from humic acid was immobilized into the membrane with composition percentage (w/w) as the following 32% of PVC, 64% of plasticizer of either [orto-nitrophenil octyl ether (NPOE) or dioctylpthalate (DOP) or dibenzyl ether (DBE)], 2% of lipophilic anion [sodiumtetraphenylborate (NaTPB), and oleic acid], and 2% of  ionophore the humic amide, respectively. The results show that ISE membrane give selective response to the Ni2+ ion at pH of 4,5 with response time of approximately 80 seconds. Among many others,  the cations that give strong emf interference include Cu2+,Li+,  K+, Pb2+, Na+, Zn2+, and Ca2+. The Nernstian factor of ISE membrane is close to +28 mV per decade with  linear range of concentration of pNi2+ of 1-6, with composition PVC membrane,  DBE as plasticizer, oleic acid as lipophilic anion, and humic amide as ionophore, respectively.